THE INFLUENCE OF MANIPULATIVE TOYS TO MATH LEARNING OUTCOMES OF 6-7 YEARS OLD CHILDREN (AN EKSPERIMEN IN 1TH CLASS OF TELUK PUCUNG ASRI VIII ELEMENTARY SCHOOL IN BEKASI) - Ardini, Pupung Puspa (Indonesian Journal of Early Childhood Education Studies, 2013)
Mathematics is the based of knowledge that children will find everyday. The application of this science was unconsciously do every day even when playing. However, in educational institutions, especially schools, learning math become a scourge that is very difficult. Thus, the study wasconducted aiming to obtain empirical data on the effect of manipulative toys of mathematics learning outcomes of children aged 6-7 years old. The method used in this study is to design experiments Randomized control group pretest-posttest. Data collection techniques using thetechniques of written test with objective form fields. After doing analysis of data, the conclusion there are differences in mathematics learning outcomes of children who are given manipulative toys and without manipulative toys. Thus, therefore to enhance the mathematical learning of children aged 6-7 years old, educators need to provide a means of manipulative play in the classroom. Then the material is delivered with a child involving the active use of tools such games.